1993
DOI: 10.1111/j.1532-5415.1993.tb02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Clinical Events in Dependent Long‐Term Nursing Home Residents

Abstract: This description of the burden on care management resulting from acute and subacute changes in clinical and functional status of chronic patients emphasizes the continuing and unpredictable nature of medical attention required in a nursing home or chronic care facility. ACEs occur far more frequently among the elderly than is generally recognized. Thus a high level of medical and nursing skill is necessary in chronic care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
(11 reference statements)
1
17
0
1
Order By: Relevance
“…No previous studies investigated the effect of AEs on hospital readmission, but our previous study [13] found that the occurrence of AEs in hospital (defined as any acute clinical problem that newly occurred during hospitalization [27]) was the most significant predictor for the extension of hospital stay by nearly 4 days and increased sevenfold the risk of in-hospital death. In this study AEs that occurred during index hospitalization were associated with the likelihood to be readmitted, confirming that also a development of a new clinical problem could represent one of the principal reasons for readmission [22].…”
Section: Discussionmentioning
confidence: 99%
“…No previous studies investigated the effect of AEs on hospital readmission, but our previous study [13] found that the occurrence of AEs in hospital (defined as any acute clinical problem that newly occurred during hospitalization [27]) was the most significant predictor for the extension of hospital stay by nearly 4 days and increased sevenfold the risk of in-hospital death. In this study AEs that occurred during index hospitalization were associated with the likelihood to be readmitted, confirming that also a development of a new clinical problem could represent one of the principal reasons for readmission [22].…”
Section: Discussionmentioning
confidence: 99%
“…drug use in community-dwelling elderly; (2) to mea¬ sure the prevalence of inappropriate drug use based on these criteria; and (3) to identify subgroups of elderly at high risk for inappropriate medication therapy.…”
Section: Discussionmentioning
confidence: 99%
“…During follow-up, we recorded Adverse Clinical Events according to the definition of Bernardini et al (18): "any acute or sub-acute change in health status, detected by specific signs, symptoms and/or laboratory findings, that suggests acute or sub-acute illness". ACEs were classified into 4 levels of severity: 1) Class A: requiring no intervention, <1 day of monitoring, without residual functional impairment; 2) Class B: requiring therapeutic intervention, 1-7 days of monitoring, without residual functional impairment; 3) Class C: requiring therapeutic intervention, 8-21 days of monitoring, without residual functional impairment; and 4) Class D: requiring therapeutic intervention and carrying residual functional impairment.…”
Section: Evaluation During Hospitalizationmentioning
confidence: 99%